Central Banking in Central and Eastern Europe : Lessons From the Interwar Years' Experience - De Cecco, Marcello (IMF Working Papers; Working Paper ;, 1994)
This paper examines the philosophies which inspired the institution of central banking in Central and Eastern Europe in the interwar years. Influenced by the Financial Section of the League of Nations, the new central banks adopted laws which prohibited or severely restricted the financing of government fiscal debt. They were encouraged to centralize their payments systems and manage exchange rates to keep control of the money supply and achieve monetary stability. Before long they were forced to adopt further provisions in the area of banking supervision to regulate commercial banks. This paper considers the particular cases of Czechoslovakia, Hungary and Poland.